2021
DOI: 10.1002/lary.29572
|View full text |Cite
|
Sign up to set email alerts
|

Mainstream Cigarette Smoke Impacts the Mouse Vocal Fold Epithelium and Mucus Barrier

Abstract: Objectives/Hypothesis Cigarette smoke (CS) is a primary risk factor for the development of numerous benign and malignant laryngeal diseases. The epithelium and mucus lining the vocal folds (VF) are the first barriers against CS. The primary objective of this study was to investigate epithelial and mucus barrier changes in the mouse laryngeal mucosa upon exposure to subacute CS. The secondary objective was to compare mucus barrier changes in mice and human smokers and nonsmokers. Study DesignAnimal model. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 51 publications
3
31
0
Order By: Relevance
“…In uninfected laryngeal tissues, the proliferation index (% Ki67 + cells) was about 1%. This is consistent with the literature reporting very few proliferating cells in adult mouse vocal folds [ 55 , 57 , 73 ]. Proliferation index increased to a median of 3.4% in diseased murine laryngeal tissues, and Ki67-expressing cells were found above the basal layer of the epithelium.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In uninfected laryngeal tissues, the proliferation index (% Ki67 + cells) was about 1%. This is consistent with the literature reporting very few proliferating cells in adult mouse vocal folds [ 55 , 57 , 73 ]. Proliferation index increased to a median of 3.4% in diseased murine laryngeal tissues, and Ki67-expressing cells were found above the basal layer of the epithelium.…”
Section: Discussionsupporting
confidence: 93%
“…Vocal fold epithelium is thinner in mice than in humans, comprising 2–4 cell layers rather than 5–10 [ 20 , 54 ]. Likely because of this difference, there is one layer of proliferating basal cells rather than two or three [ 54 , 55 , 56 , 57 ]. The same markers of basal cells (p63), proliferating cells (Ki67), differentiated cells (cytokeratin 13 (K13)), cell–cell junctions (E-cadherin, β-catenin, zonula occludens 1 (ZO-1)), and basement membrane (laminin, collagen IV) are present in the vocal fold epithelium of humans [ 20 , 21 , 22 , 34 , 58 , 59 , 60 ] and mice [ 34 , 47 , 54 , 55 , 56 , 57 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mainstream CS from Kentucky 3R4F reference cigarettes was generated using inExpose smoking equipment (SCIREQ, Montreal, QB, Canada), consistent with our previous studies [12][13][14] . Exposure conditions were per the Federal Trade Commission (FTC)/International Standard Organization (ISO) standards (ISO 1991).…”
Section: Cigarette Smoke Generationmentioning
confidence: 92%
“…HD mice were exposed to 4 h of CS per day in 1-1.5 h increments, with room air breaks. Earlier studies in the airways and speci cally in the larynx, have shown that 1-4 h/day of CSE is su cient to induce histopathological changes 12,13,77,78 . LD and HD CS exposures were performed for 5 days/week, M-F for a total of 4 weeks as per the subacute inhalation toxicity guidelines regulated by the Organization for Economic Co-operation and Development (OECD) 79 .…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation